Impact of sense of coherence on oral health-related quality of life among Brazilian adults - Evely Sartorti da SILVA; Rosana de Fátima POSSOBON; Marcela Di Moura BARBOSA; Marília Jesus BATISTA; Livia Maria Andaló TENUTA (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract It has been postulated that oral health-related quality of life (OHRQoL) may be affected by the sense of coherence (SOC), but there are no epidemiological studies investigating this association in Brazilian adults. The present study was conducted among adults of a mid-sized Brazilian city, with the aim of looking into this association. The probability sampling consisted of 342 adults aged 35-44 years old, from a mid-sized Brazilian city, who were examined at their homes for caries (Decayed, Missing and Filled Teeth [DMFT] Index) and periodontal disease (Community Periodontal Index - CPI), according to WHO criteria. The questionnaire applied included demographic factors, socioeconomic information, use of dental services, behavior, SOC and the Oral Health Impact Profile (OHIP). The OHIP outcome, measured by prevalence of the impact, was analyzed by binary logistic regression using a hierarchical approach, a conceptual model, and a 5% significance level. A total of 67.9% of the respondents had one or more impacts on OHRQoL, and 54.4% showed a high SOC. The impact on OHRQoL was more prevalent in adults who had a manual occupation (PR = 2.47, 95%CI 1.24-4.93), those who perceived the need for dental treatment (PR = 2.93, 95%CI 1.67-5.14), and those who had untreated caries (PR = 1.93, 95%CI 1.07-3.47). Those with a low SOC had a twofold higher prevalence of impact on OHRQoL (PR = 2.19, 95%CI 1.29-3.71). This impact on OHRQoL was associated with a low SOC, even after adjusted by socioeconomic, behavioral and clinical factors. Future studies should consider the SOC in determining the oral health impact on quality of life.